BIO CRUDE OIL PRODUCTION BY PYROLYSIS OF CRUDE PALM OIL USING THERMALLY ACTIVATED BENTONITE AS CATALYST - Kamisah Pandiangan; Wasinton Simanjuntak; Ilim Ilim; Diky Hidayat; Adryan Daffa Dzulfiqar; Aditya Anugrah Sahyani; Giovani Ramadhan; Tyas Nurfitria (Jurusan Kimia FMIPA Universitas Lampung, 2025)
In this research, crude palm oil (CPO) was subjected to pyrolysis treatment for the production of bio-crude oil (BCO) using thermally activated bentonite as a catalyst. The bentonite was subjected to calcination for 8 hours at 600, 700, and 800 oC, respectively. The original and activated bentonite samples were then characterized using XRD and SEM in order to evaluate the effect of calcination temperatures on structure and microstructure of the samples. Subsequently, the samples were used as catalyst for pyrolysis of CPO, and the BCO samples were analyzed using GC-MS. The results indicate that hydrocarbons are the dominant components of the BCO samples, suggesting that bentonite has promising potential as a catalyst for production of biohydrocarbons from biomass by pyrolysis. It was also found that the BCO with the highest biohydrocarbons content of 76.45% was produced with the use of bentonite calcined at 800 oC as catalyst.